Análisis del índice de selección del programa de mejoramiento genético sostenible de bovinos de leche en la parroquia Mulaló, en el periodo 2023 - Casa Toapanta, Jhoselyn Stefania (2024)
The present research project focused on analyzing the selection index of the genetic improvement program for dairy cattle in the parish of Mulaló, Cotopaxi, Ecuador, a region of outstanding dairy production. Data were collected from 71 animals and 11 producers during the months of October, November and December 2023, covering production costs, GDP, production at 305 days, density and height at withers. The results showed an average production cost of $0.26 per liter of milk, with feed being the most significant expense (40% of the total). Although the average monthly profit was approximately $728.42, reliability was low due to lack of records. Genetic values were determined for the characteristics evaluated, highlighting the importance of lactation at 305 days. The values obtained for GDP had an estimated maximum point of 148.37; for density, a maximum peak of 4.81, considering that it will be added to the estimated mean; for lactation at 305 days, with maximum peaks of 1005.81; and for height at withers a maximum peak of 15.46 cm. The analysis of the selection index allowed identifying Juliana, a Holstein breed, standing out in GDP; Barrosa, a Pizán breed, excelled in milk production; Preciosa, a Holstein breed, showed excellence in milk density; and Angelita, also a Holstein breed, stood out in centimeters at the withers. All these findings are related to the response to selection within the genetic improvement program for dairy cattle in Mulaló.